MASS CUSTOMIZATION IN SERVICE OPERATIONS - An, Wang (2010)
Abstract The concept of Mass customization (MC) is the ability to provide individually designed products and services to each customer through high process flexibility and integration. In recent years, MC has been identified as a competitive strategy; however, the investigations of MC in the service context are limited. In this dissertation, the published classification of MC approaches have been discussed and tested through cases which are from four different service industries. The limitations of these methods and the main characteristics which they have not covered have been highlighted. The analysis of the findings leads to the development of a service operations process framework, which comprises five fundamental service MC modes based on the framework of MC modes for manufacturing developed by MacCarthy et al. (2003). The framework and models have been extended through integrating modularity approach in order to improve the ability of full utilization of operations resource in the service industries. Some feasible approaches related to the application of modularity approaches have been suggested for the enterprises, who adopt mass customization strategy, in the service industry.